THE EVALUATION OF THE COMPARISON ANTITUBERCULOSIS DRUGS INTERACTIONS TO THE TEENAGER AND ADULT INPATIENT AT LABUANG BAJI HOSPITAL MAKASSAR IN 2019 - Ummu Kalsum; Nurhikma Awaluddin; Susanti Ngole Dhadu (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
ABSTRACT Background : The drugs interaction is a changes of the drugs due effect because of the combination with another drugs or the consumtion of the drugs in the same time. The drugs interaction will make a reduction of the drugs effect so that the result of the therapy is not as good as the expectation. The research of the drug interaction is to reduce and prevent the treatment fo the tuberculosis patient with a right treatment so it will reduce the drugs interaction during the therapy and also can increase a good therapy which is can effective, safe and efficient. The aim of the research was to known the interaction antituberculosis drugs to the teenager and adult inpatient in the RSUD Labuang Baji Makassar 2019. Methods : The method of the research was used non-experimental (observational) descriptive analysis (qualitative) and retrospective data collection. In this research, there were 62 samples by used Slovin's formula technique. The drugs interaction in terms of Drug interaction of Stockley's book in 9th edition. Checker drugs interaction application and Medscape application. Result : The result of the research showed the interaction of the antituberculosis drugs and non antituberculosis drugs ware 62 cases (100%). The evaluation of the interaction antituberculosis drugs : The severity or the significance highest level were 34 cases (75.6%), based on the data collection in the patient who consumed Isoniazid. That medicine was used for tuberculosis treatment therapy category 1, category 2 and multi drugs resistant. Based on mechanism showed pharmacodynamics were 24 cases (53.3%). Then based on the data collection showed the most of pharmacodynamics level interaction was Moxifloxacin doe to used for the treatment of multi drug resistant of tuberculosis. In this research, the most patient was multi drug resistance of tuberculosis. Based on the interaction of pharmacodynamics level showed that antagonist was the highest level with 22 cases (91.7%). Conclusion : Based on the data collection showed the most interaction of the highest antagonist was Moxifloxacin due to used as multi drug resistant of tuberculosis. Keywords: Antituberculosis, Drug Interaction, Labuang Baji Hospital.